Labor Productivity as an Indicator of Efficiency Interaction of Higher Education and Tourism Business - DRAKH, Tatyana Pavlovna; SALZHANOVA, Zaure Abildinovna; ALPEISSOVA, Sholpan Esenbaevna; KOZHAKHMETOVA, Maral Kenebaevna; KAZKENOVA, Aigul; SABIROVA, Rysty; OMARKHANOVA, Zhibek Maksutovna (Journal of Environmental Management and Tourism; Vol 12 No 2 (2021): JEMT Volume XII Issue 2(50) Spring 2021, 2021)
The development of the tourism industry is directly related to the training and retraining, professional development of tourist personnel, as it is an update of the theoretical and practical knowledge of staff in accordance with the increasing requirements of the market economy. This article examines the possibilities of increasing labor productivity due to the influence of the tourist business sector on the sphere of higher education. The purpose of this study is to substantiate the interaction of universities and the tourism business sector to increase labor productivity in Kazakhstan as an indicator of the competitiveness of the tourism industry and the higher education sector. The article presents the results of models of multi-factor analysis to study the relationship and influence of some indicators of education and science on the labor productivity of the tourist business sector and academic productivity in Kazakhstan. According to the analysis, the most significant factors are the financing of higher education and the wage fund of universities. The study concludes that the interaction of higher education institutions with the tourism business will increase the financial income of universities that provide services to the tourism business, which, in turn, will improve the ability of universities to increase wage bill to motivate scientists to interact with the tourism business.